Analisis Regulasi Kewenangan Bidang Pertanahan di Kota Batam - A. M. Rusli; Andi Lukman Irwan; Azura Adawiyah Rahman (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2021)
Determining the status of Batam Island as an industrial area through Presidential Decree Number of 41 in 1973 on the Establishment area of the Batam Authority Developers Batam Industrial experience a change in the pattern of policies in the industrial field but also in the sectors of land, this can be seen with the establishment of the Presidential Decree number 41 in 1973 which regulates the formation of industry but also in the land sector. This can be seen with the formation of the Interior Minister Decree Number 43 in 1977 regulating the management and use of land in the industrial island of Batam granted rights management (HPL) to Batam Entrepreneurs Bureau. With the enactment of 23 in 2014 on local governments, so that the authorities in the land sector there is a division of authority and in the implementation of the municipality with the Agency Employers do not run smoothly in because of overlapping authority.